TLR2/MyD88/NF-κB Pathway, Reactive Oxygen Species, Potassium Efflux Activates NLRP3/ASC Inflammasome during Respiratory Syncytial Virus Infection - Segovia, Jesus; Sabbah, Ahmed; Mgbemena, Victoria; Tsai, Su-Yu; Chang, Te-Hung; Berton, Michael T.; Morris, Ian R.; Allen, Irving C.; Ting, Jenny P.-Y.; Bose, Santanu (PLOS ONE, 2012)
Human respiratory syncytial virus (RSV) constitute highly pathogenic virus that cause severe respiratory diseases in newborn, children, elderly and immuno-compromised individuals. Airway inflammation is a critical regulator of disease outcome in RSV infected hosts. Although “controlled” inflammation is required for virus clearance, aberrant and exaggerated inflammation during RSV infection results in development of inflammatory diseases like pneumonia and bronchiolitis. Interleukin-1β (IL-1β) plays an important role in inflammation by orchestrating the pro-inflammatory response. IL-1β is synthesized as an immature pro-IL-1β form. It is cleaved by activated caspase-1 to yield mature IL-1β that is secreted extracellularly. Activation of caspase-1 is mediated by a multi-protein complex known as the inflammasome. Although RSV infection results in IL-1β release, the mechanism is unknown. Here in, we have characterized the mechanism of IL-1β secretion following RSV infection. Our study revealed that NLRP3/ASC inflammasome activation is crucial for IL-1β production during RSV infection. Further studies illustrated that prior to inflammasome formation; the “first signal” constitutes activation of toll-like receptor-2 (TLR2)/MyD88/NF-κB pathway. TLR2/MyD88/NF-κB signaling is required for pro-IL-1β and NLRP3 gene expression during RSV infection. Following expression of these genes, two “second signals” are essential for triggering inflammasome activation. Intracellular reactive oxygen species (ROS) and potassium (K+) efflux due to stimulation of ATP-sensitive ion channel promote inflammasome activation following RSV infection. Thus, our studies have underscored the requirement of TLR2/MyD88/NF-κB pathway (first signal) and ROS/potassium efflux (second signal) for NLRP3/ASC inflammasome formation, leading to caspase-1 activation and subsequent IL-1β release during RSV infection.